The Correlation Of Ujian Tahap Bersama (UTB) With Grade Point Average (GPA) - Shafira, Nyimas Natasha Ayu; Nabila, Risa; Tarawifa, Susan (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACT Background: There are several assessments in medical education in Indonesia.  Currently, as a formative assessment at the preclinical level, UTB (Ujian Tahap Bersama) is being proposed to control the quality of medical education graduates. Objective: This study aims to determine the correlation between UTB scores and Grade Point Average  (GPA). Methods: This study was an analytic study with a cross-sectional design using a total sampling technique. The sample of this study was students participating in UTB Stage 1 or UTB Stage 2 at the Medical Study Program, Faculty of Medicine and Health Science Jambi University. Result: The average UTB Stage I score was 36.83±8.86, and the average UTB Stage II score was 45.42±7.43. There was a correlation between UTB Stage I score and GPA  (p <0.001), with a coefficient correlation of 0.677. There was a correlation between UTB Stage II score and GPA (p<0.001), with a coefficient correlation of 0.575. Conclusion: There was a strong correlation between UTB Stage I scores and GPA and a moderate correlation between UTB Stage II scores and GPA.